Nanomechanics of imperfectly straight single walled carbon nanotubes under axial compression by using molecular dynamics simulation - Wong, C. H. (2013)
The buckling characteristics of several curved forms of single walled carbon nanotubes (SWCNTs) were studied in this work via molecular dynamics simulation method. The structural morphology of the CNT was modified to induce curvature along the tube axis. The nature of mechanical properties of these classes of CNTs under compression deviates from the ideal ‘perfectly straight’ CNTs. We found that the inclusion of curvature along the tube axis can significantly impact the performance of the carbon nanotube under compression. These curvilinear CNTs, when combined with other CNTs to form a bundle, will have a greater weakening effect on the mechanical performance of the CNT bundle.